Simultaneous assessment of mechanical and electrical function in Langendorff-perfused ex-vivo mouse hearts - Louradour, Julien; Ottersberg, Rahel; Segiser, Adrian; Olejnik, Agnieszka; Martínez-Salazar, Berenice; Siegrist, Mark; Egle, Manuel; Barbieri, Miriam; Nimani, Saranda; Alerni, Nicolò; Döring, Yvonne; Odening, Katja E.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The Langendorff-perfused ex-vivo isolated heart model has been extensively used to study cardiac function for many years. However, electrical and mechanical function are often studied separately—despite growing proof of a complex electro-mechanical interaction in cardiac physiology and pathology. Therefore, we developed an isolated mouse heart perfusion system that allows simultaneous recording of electrical and mechanical function. Methods Isolated mouse hearts were mounted on a Langendorff setup and electrical function was assessed via a pseudo-ECG and an octapolar catheter inserted in the right atrium and ventricle. Mechanical function was simultaneously assessed via a balloon inserted into the left ventricle coupled with pressure determination. Hearts were then submitted to an ischemia-reperfusion protocol. Results At baseline, heart rate, PR and QT intervals, intra-atrial and intra-ventricular conduction times, as well as ventricular effective refractory period, could be measured as parameters of cardiac electrical function. Left ventricular developed pressure (DP), left ventricular work (DP-heart rate product) and maximal velocities of contraction and relaxation were used to assess cardiac mechanical function. Cardiac arrhythmias were observed with episodes of bigeminy during which DP was significantly increased compared to that of sinus rhythm episodes. In addition, the extrasystole-triggered contraction was only 50% of that of sinus rhythm, recapitulating the “pulse deficit” phenomenon observed in bigeminy patients. After ischemia, the mechanical function significantly decreased and slowly recovered during reperfusion while most of the electrical parameters remained unchanged. Finally, the same electro-mechanical interaction during episodes of bigeminy at baseline was observed during reperfusion. Conclusion Our modified Langendorff setup allows simultaneous recording of electrical and mechanical function on a beat-to-beat scale and can be used to study electro-mechanical interaction in isolated mouse hearts.